Developing an Ethnoscience-Based Snakes and Ladders Board Game to Enhance Gross Motor Skills and Independence in Children with Speech Impairments - Agrielsa Alphasati Sinaga; Yunita Miftahul Jannah; Christina Ester Manthalina Hutabarat (Postgraduate, University of Mataram, 2026)
This study aims to develop an ethnoscience-based snakes and ladders board game as a learning medium to improve integrated gross motor skills and independence of students with speech impairments at the junior high school (SMP) level in inclusive education settings. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Gross motor skills were defined as coordinated movement abilities involving balance, body control, and dynamic coordination relevant to adolescents with speech impairments, while independence was defined as the ability of self-regulation, decision-making, task completion, and responsibility in learning activities. The research subjects were 15 seventh-grade students with speech impairments at SLB Negeri 1 Bantul, Yogyakarta. Data were collected through observation sheets, expert validation questionnaires, and assessment instruments for gross motor skills and independence. The validation results indicated that the developed media were highly feasible, with average scores of 91% from material experts and 89% from media experts. Limited trials demonstrated improvements in gross motor skills (mean scores increased from 64.3 to 80.7) and independence (from 66.1 to 83.5), with N-gain values in the moderate to high category. Ethnoscience elements were integrated through local cultural contexts such as traditional games, batik motifs, and Yogyakarta cultural symbols embedded in science learning challenges. These findings indicate that the ethnoscience-based snakes and ladders board game is effective as an alternative learning medium for students with speech impairments at the junior high school level.